The Effect of Self-Regulation on Social Emotional Skills in Early Childhood - Sitinjak, Mika; Puridawaty, Brigita (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2024)
This study was conducted to determine the effect of self-regulation on the social-emotional abilities of group B children at PT’s Kindergarten. The type of research used is quantitative research with a correlational approach, or non-experimental research, which is almost the same as ex facto research. This study used a sample of 20 children in group B. The instrument used was a questionnaire, while the data analysis in this study used SPSS 22. Based on the results of the study, it was shown that there was an influence of self-regulation on the social-emotional abilities of Group B children at PT’s Kindergarten. With a significance value (Sig.) of  0.000 less than a probability of  0.05, it can be concluded that H0 is rejected and Ha is accepted, which means that "there is an effect of self-regulation (X) on the child's social-emotional ability (Y)". The results of the coefficient of determination in the regression model with an adjusted R2 value of 0.808 can be interpreted as indicating that 80.8 percent of children's interpersonal intelligence can be explained by self-regulation. While the remaining 19.2 percent was influenced by other variables that were not included in this research model.